Stem Cells - J M W Slack (Very short introductions, 303., 2012)
Embryonic stem cells have been hot-button topics in recent years, generating intense public interest as well as much confusion and misinformation. In this Very Short Introduction, leading authority Jonathan Slack offers a clear and informative overview of stem cells--what they are, what scientists do with them, what stem cell therapies are available today, and how they might be used in the future. Slack explains the difference between embryonic stem cells, which exist only in laboratory cultures, and tissue-specific stem cells, which exist in our bodies, and he discusses how embryonic stem cells may be used in the future to treat such illnesses as diabetes, Parkinson\'s disease, heart disease, spinal trauma, and retinal degeneration. But he stresses that, despite important advances, the clinical applications of stem cells are still in their infancy and that most real stem cell therapy today is some form of bone marrow transplantation. Slack concludes by analyzing how medical innovation has occurred in this area in recent years and he draws out some of the lessons for the development of new therapies in the future.